ANALISIS MANAJEMEN LABA USAHA KEDAI KOPI PADA MASA PANDEMIK COVID-19 DI KELURAHAN AMBAN MANOKWARI BARAT - Nurwidianto Nurwidianto; Sarah Usman; Nurul Hikmah (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2021)
This research aims to look at how the financial understanding of coffee shop business owners, and to see how the profit management of coffee shop business owners. This research uses a qualitative method research design with descriptive explanations. The method used in the sample is area sampling. The population in this study was a coffee shop. Samples in this study met 7 coffee shops. Data collection techniques use observation and interviews. The results of this study show that: (1) The financial understanding owned by coffee shop business owners 100% can distinguish the participation and expenditure. 90% of coffee shop owners have understood financial record keeping for cooking and expenses. 20% of coffee shop owners can identify the risks that exist in their business. 40% of coffee shop owners set up businesses with their own capital. (2) The management of profits owned by the owner's coffee shop business there are as much as 70% has compiled and planned provisions regarding the amount of profit received from the sale. 40% of owners have drafted their business finance plan.